Cutaneous Recording and Stimulation of Muscles Using Organic Electronic Textiles. Issue 16 (31st May 2016) - Papaiordanidou, Maria; Takamatsu, Seiichi; Rezaei‐Mazinani, Shahab; Lonjaret, Thomas; Martin, Alain; Ismailova, Esma
Abstract : Electronic textiles are an emerging field providing novel and non‐intrusive solutions for healthcare. Conducting polymer‐coated textiles enable a new generation of fully organic surface electrodes for electrophysiological evaluations. Textile electrodes are able to assess high quality muscular monitoring and to perform transcutaneous electrical stimulation.